Exploring Organisational Controversies as Actor-Networks: Ethnographic Insights from a Brazilian State School - Americo Bruno Luiz; Tureta César; Clegg Stewart Roger (Journal of Organizational Sociology)
We adopt an ethnographic approach grounded in Actor-Network Theory (ANT) to examine the controversies surrounding student performance in a Brazilian State School recovering from a post-disaster scenario. By tracing the networks of actors – school staff, students, educational regulations, and community concerns – we illustrate how translation processes shape and stabilise organisational actions. The analysis reveals that controversies over project-based versus traditional learning approaches prompted continuous renegotiation of roles, interests, and goals. These renegotiations drew on output-based regulations, prior award-winning educational projects, and local socio-environmental issues to enact a provisional future that the school should achieve. Our findings suggest that contradictory interests in highly regulated public institutions do not necessarily mean a lack of success in achieving collective objectives but instead create opportunities for their creative redefinition. We demonstrate how past experiences and imagined futures influence public managers’ and employees’ decisions in negotiating these controversies, temporarily stabilising organisational practices.